The Field Trip as Part of Spatial (Architectural) Design Art Classes - Janja Batič (Center for Educational Policy Studies Journal, 2018)
Spatial (architectural) design is one of five fields introduced to pupils as part of art education. In planning architectural design tasks, one should take into consideration the particularities of the architectural design process and enable pupils to experience space and relationships within space through their own movement. Furthermore, pupils should have an opportunity to play the roles of (critical) users as well as co-creators or spatial planners. In this respect, the field trip plays a vital role, as it allows pupils to experience (architectural) space through their own movement, their senses and in a real environment. The architectural experience that the pupils gain differs from their everyday experience of moving through space, as the former is based on education and training, and thus helps pupils develop architecture appreciation.